Non-surgical management of iatrogenic aortic dissection (Dunning class 3) caused by percutaneous coronary intervention - B. Gryko, Adam; Chlabicz, Małgorzata; Jakim, Piotr; S. Nowak, Konrad; Bachórzewska-Gajewska, Hanna; Dobrzycki, Sławomir (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Iatrogenic aortic dissection (IAD) is a rare complication of catheter-based coronary procedures. It occurs with a frequency of 0.006% during coronary angiography and 0.098% during interventional procedures [1]. It more often concerns the right coronary artery (RCA) and patients with acute coronary syndrome. In 2000, Dunning et al. divided IAD into 3 types [2]. Class 1 was limited to the aortic sinus, class 2 involved less than 4 cm of the ascending aorta and class 3, the most dangerous, exceeded 4 cm in length. Therapeutic recommendations for IAD are still scarce, but recent reports suggest that even class 3 IAD can be treated conservatively or by placing a stent [1, 3]. We would like to present a case of iatrogenic aortic dissection (Dunning class 3) as a complication of RCA angioplasty.